Mutations in TNK2 in severe autosomal recessive infantile onset epilepsy. Issue 3 (4th September 2013) - Hitomi, Yuki; Heinzen, Erin L.; Donatello, Simona; Dahl, Hans‐Henrik; Damiano, John A.; McMahon, Jacinta M.; Berkovic, Samuel F.; Scheffer, Ingrid E.; Legros, Benjamin; Rai, Myriam; Weckhuysen, Sarah; Suls, Arvid; et al.
<x xml:space="preserve">Abstract</x> We identified a small family with autosomal recessive, infantile onset epilepsy and intellectual disability. Exome sequencing identified a homozygous missense variant in the gene TNK2, encoding a brain‐expressed tyrosine kinase. Sequencing of the coding region of TNK2 in 110 patients with a similar phenotype failed to detect further homozygote or compound heterozygote mutations. Pathogenicity of the variant is supported by the results of our functional studies, which demonstrated that the variant abolishes NEDD4 binding to TNK2, preventing its degradation after epidermal growth factor stimulation. Definitive proof of pathogenicity will require confirmation in unrelated patients. Ann Neurol 2013;74:496–501